Water bugs (Hemipera: Heteroptera: Nepomorpha & Gerromorpha) of Chile: phylogenetic and biogeographic considerations, and a catalog of the fauna - Damgaard, Jakob; Moreira, Felipe Ferraz Figueiredo (Zootaxa, 2021)
The Chilean fauna of water bugs comprises seven species of semi-aquatic bugs (Heteroptera: Gerromorpha), representing five genera, three tribes, four subfamilies and four families; and 27 species and one subspecies of aquatic bugs (Heteroptera: Nepomorpha), representing four subgenera, eight genera, three tribes, seven subfamilies, and five families. We compare the fauna with neighboring countries and find that several otherwise widespread and abundant taxa are missing in Chile, but that Chepuvelia usingeri China, 1963 (Macroveliidae), Microvelia chilena Drake & Hussey, 1955 (Veliidae), Limnocoris dubiosus Montandon, 1898 (Naucoridae), Nerthra (Nerthra) parvula (Signoret, 1863), N. (N.) undosa Nieser & Chen, 1992, N. (Rhinodermacoris) praecipua Todd, 1957 (Gelastocoridae), and Sigara (Tropocorixa) termasensis (Hungerford, 1928a) (Corixidae) are endemic to the country. To this list, we add †Nerthra (Nerthra) subantarctica Faúndez & Ashworth, 2015, even though the species is only known from a subfossil. We can also inform that while water bugs are found in the archipelagoes of southern Chile, no species has been reported from the Juan Fernandez Islands, Easter Island and other off-shore islands. Several of the Chilean species are without any close extant relatives, such as C. usingeri and Aquarius chilensis (Berg, 1881) (Gerridae), or with relatives in Oceania (N. praecipua), suggesting that historical events such as dispersal and extinction have had a major influence on the composition of the Chilean fauna.